2012
DOI: 10.1200/jco.2012.42.8466
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Care and Pursuit of Active Surveillance in Low-Risk Prostate Cancer

Abstract: Multidisciplinary care is associated with increased selection of active surveillance in men with low-risk prostate cancer. This finding may have an important clinical, social, and economic impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(62 citation statements)
references
References 26 publications
4
58
0
Order By: Relevance
“…Spouses of these married patients may encourage them to perform surgery versus expectant management 28, which could partly account for the discrepancies. Studies showed diagnosis of cancer caused more distress than other diseases 29.…”
Section: Discussionmentioning
confidence: 99%
“…Spouses of these married patients may encourage them to perform surgery versus expectant management 28, which could partly account for the discrepancies. Studies showed diagnosis of cancer caused more distress than other diseases 29.…”
Section: Discussionmentioning
confidence: 99%
“…Although one correlational study detected that patients from multidisciplinary clinics were more likely to receive AS than patients under the care of individual practitioners, 46 there is insufficient evidence to address the factors affecting the offer of, acceptance of, and adherence to AS. There is also insufficient evidence to make recommendations with regard to the personnel who should be responsible for the management of AS protocols.…”
Section: Further Qualifying Statementsmentioning
confidence: 99%
“…After a long discussion it was decided, at least for the initial phase of the implementation, to leave the number as 50 in order to facilitate the organization of PCU in centers not particularly focused on prostate surgery. In addition, the evaluation of the case load of a PCU must pay particular attention to the number of patients on active surveillance, who should be considered as patients potentially undergoing radical treatments [33,37,38]. Another significant point of discussion was the mandatory participation of the uro-pathologists in the Interdisciplinary and Multiprofessional Team Meetings as member of the Core Team.…”
Section: Pcu Treatment and Observational Settingmentioning
confidence: 99%
“…Centers systematically proposing active surveillance are experiencing a decrease in the number of patients undergoing prostatectomy, radiotherapy or brachytherapy [33,37,38]. This new scenario was considered when the mandatory number of radical procedures was decided.…”
Section: Pcu Treatment and Observational Settingmentioning
confidence: 99%